2018
DOI: 10.3390/mca23030032
|View full text |Cite
|
Sign up to set email alerts
|

Total Controllability of the Second Order Semi-Linear Differential Equation with Infinite Delay and Non-Instantaneous Impulses

Abstract: Abstract:In this manuscript, a stronger concept of exact controllability called Total Controllability has been introduced. Sufficient conditions have been established for the total controllability of the proposed problem. The proposed control problem is a second-order semi-linear differential equation with infinite delay and non-instantaneous impulses. The tools for study include the strongly continuous cosine family and Sadovskii's fixed point theorem. The cosine family and the nonlinear function associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…corresponding to the three terms in expression (5). Then, expanding the binomial terms and rearranging and renaming indices, one has…”
Section: Proof Writementioning
confidence: 99%
See 1 more Smart Citation
“…corresponding to the three terms in expression (5). Then, expanding the binomial terms and rearranging and renaming indices, one has…”
Section: Proof Writementioning
confidence: 99%
“…Due to the presence of time lags in the dynamics of most real systems, delay differential equations (DDE) have become basic instruments in the mathematical modelling of a wide range of problems in science and engineering, such as in population biology, physiology, epidemiology, economics, and control problems (see, e.g., [1][2][3][4][5], and references therein), and special methods have been developed to compute numerical solutions for DDE [6]. In the case of differential problems without delay, exact schemes have been defined for different particular problems, and the use of nonstandard finite difference (NSFD) numerical schemes has gained increasing interest in the last years [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Since B is a bounded linear operator from H to X, the above convergence also implies 13) for all t ∈ J. Here, we used the weak convergence given in (3.12) and the compactness of the operator (Qf )(…”
Section: Proof Let Us First Definementioning
confidence: 99%
“…Controllability plays a vital role in designing and analyzing control systems. The theory of controllability of the first and second order deterministic or stochastic systems in infinite dimensional spaces is well developed, and has been studied extensively, see for instance [6,7,8,10,13,16,28,31,42], etc. Controllability means that a dynamical system can be steered to the desired final state constrained to an admissible class of controls.…”
mentioning
confidence: 99%
“…It deals with whether or not the state of a state-space dynamic system can be controlled from the input. Many authors dealt with controllability problems that can be found in many recently published papers [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%